Turkey : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Turkey. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation with Turkey discusses that economic growth has since resumed, buoyed by expansionary fiscal policy, rapid credit provision by state-owned banks, and more favorable external financing conditions. The lira also recovered as market pressures abated. Import compression and a strong tourism season have contributed to a remarkable current account adjustment. Inflation has fallen sharply, and the central bank cut policy rates by 1000 basis points since July 2019. Inflation peaked at around 25 percent-five times the target-in October 2018 due, in large part, to high exchange rate passthrough and rising inflation expectations. However, strong base effects, relative lira stability, and a negative output gap have since contributed to a steep inflation decline, although inflation expectations remain well above target. State-owned banks are supporting rapid credit growth. While private banks have cut back on their lending, state-owned banks have engaged in a major credit expansion which picked up pace in early-2019.